If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = 4u + 4 Reorder the terms: -12 = 4 + 4u Solving -12 = 4 + 4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-4u' to each side of the equation. -12 + -4u = 4 + 4u + -4u Combine like terms: 4u + -4u = 0 -12 + -4u = 4 + 0 -12 + -4u = 4 Add '12' to each side of the equation. -12 + 12 + -4u = 4 + 12 Combine like terms: -12 + 12 = 0 0 + -4u = 4 + 12 -4u = 4 + 12 Combine like terms: 4 + 12 = 16 -4u = 16 Divide each side by '-4'. u = -4 Simplifying u = -4
| 2(v+1)=3v+23 | | 3(x+5)+6=-6 | | 1/3x^2-10x | | -2a+7=-23 | | 3(y+4)-2y=2(y+1) | | (2x+4)9=(3x-30)9 | | 2(v+1)=3u+23 | | x=3x+6x-9 | | x^3-6x^2-20x+120=0 | | 4t+3m=1529 | | log^3=1 | | -2-5b+8b=-8(-3-6b)-5(8+6b) | | 6(-2)-y=-18 | | 6y=49-y | | 2a+a=39 | | 7w=w+18 | | -7v+6=-36 | | 6(3)-y=-18 | | 2.4=02 | | a+1-2a-1E+1=2 | | y=3x+6x-9 | | 8x-15y=0 | | a+b-(ab)=1 | | 6(2)-y=-18 | | ba=a+b+1 | | 3(c+3)+8=-10 | | 2[x+9]=x+22 | | a+b+2=ba | | -5a+4+6a=10-19 | | -3(2x+1)+20=8x+5 | | 384-6x^2=0 | | 5=20a |